Gambaran Father Involvement pada Remaja di Kota Bandung - Sarah Nurul Fathanah; Indri Utami Sumaryanti (UNISBA Press, 2024)
Abstract. Late adolescence shows major problems with eating problem, school, aggression, substance use, depression and sexual relationships. Father involvement is particularly important as a mentor and protector for adolescents. The city of Bandung has shown strong interest in father involvement as evidenced by the establishment of a father's school and programs specifically aimed for fathers. This study aims to describe father involvement among late adolescents in Bandung City. The research used descriptive study method with quantitative approach. The measuring instrument used is the Perceived Father Involvement Inventory (PFII) which measures father involvement from the child's perspective. Data analysis used descriptive statistics. The results showed that most fathers in Bandung City showed high involvement (50.1%) with the highest dimension shown in paternal responsibility or the father's ability to be responsible for adolescents and their families (Mean = 72.774) and the lowest dimension was paternal engagement or direct activity/interaction with adolescents (Mean = 69.838). Abstrak. Pada masa remaja akhir menunjukkan adanya permasalahan-permasalahan utama dalam masalah makan, sekolah, agresi, penggunaan/penyalahgunaan obat-obatan, depresi dan hubungan seksual. Keterlibatan ayah (father involvement) menjadi penting khususnya sebagai pembimbing dan pelindung bagi remaja. Kota Bandung menunjukkan perhatian yang kuat dalam masalah keterlibatan ayah dilihat dari dibentuknya sekolah ayah dan program-program yang khusus ditujukan bagi ayah. Penelitian ini bertujuan untuk menggambarkan father involvement pada remaja akhir di Kota Bandung. Penelitian menggunakan metode studi deskriptif dengan pendekatan kuantitatif. Alat ukur yang digunakan adalah Perceived Father Involvement Inventory (PFII) yang mengukur keterlibatan ayah dari perspektif anak. Analisis data menggunakan statistik deskriptif. Hasil menunjukkan bahwa sebagian besar Ayah di Kota Bandung menunjukkan keterlibatan yang tinggi (50,1%) dengan dimensi tertinggi ditunjukkan pada paternal responsibility atau kemampuan ayah dalam bertanggung jawab pada remaja dan keluarganya (Mean=72,774) serta dimensi terendahnya adalah paternal engagement atau aktivitas/interaksi langsung dengan remaja (Mean=69,838).